Bilateral imbalances in Europe - Helge Berger; Volker Nitsch (Technische Universität Darmstadt, Department of Law and Economics, 2012)
This paper examines the association between trade and financial linkages among European countries. We find that, with the introduction of the euro, trade imbalances among euro area members widened considerably, even after allowing for permanent asymmetries in trade competitiveness within pairs of countries or in the overall trade competitiveness of individual countries. Moreover, there is a significant relationship between patterns of trade and bilateral financial linkages, especially within the euro area; a surplus of a country in a bilateral trade relationship is typically accompanied by a country's positive net financial position vis-à-vis the respective partner country.
Keywords: F15; F16; F32; F36; F42; 330; trade balance; international investment position; euro; EMU; European integration; Handelsbilanz; Außenwirtschaftliches Gleichgewicht; Auslandsvermögen; Eurozone; Eurozone